The Principal's Leadership Style in the Implementation of the Independent Curriculum at Lamandau Regency, Central Kalimantan Province - Ismi Nurul Aslamiah; Meilina Bustari (FKIP - Universitas Riau, 2026)
This study aims to describe the leadership styles of principals in implementing the Independent Curriculum, analyze the supporting and inhibiting factors of principal leadership, and identify leadership strategies that support the successful implementation of the Independent Curriculum at SMA Negeri 1 Sematu Jaya and SMA Negeri 1 Nanga Bulik. This is a descriptive qualitative study with principals, teachers, and students as subjects. Data collection was conducted through in-depth interviews, observations, and documentation studies. Data were analyzed using the interactive model of Miles, Huberman, and Saldaña, which includes data collection, data condensation, data presentation, and conclusion. The results indicate that: (1) the leadership styles of principals in both schools are dominated by democratic leadership, characterized by open communication and teacher involvement in decision-making; (2) supporting factors include teacher professional commitment, a collaborative culture, and support for school policies, while inhibiting factors include uneven pedagogical readiness and technological literacy among teachers, limited digital learning facilities, and geographical conditions; and (3) leadership strategies are realized through needs-based planning, strengthening teacher professional capacity, and collaborative resource management.